Managing Crisis in Education: The Role of Digital Leadership and Social Media Communication - Abidin, Zainal; Qusairi, Ahmad; Mubarak, Fadhel (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze effective leadership strategies and practices in utilizing social media in a responsive, empathetic, and transparent manner during a crisis. Using a qualitative case study approach, the research involved in-depth interviews with 30 informants, direct observation, and documentation. Data were analyzed thematically with reference to theories of transformational leadership, digital communication, and crisis management. The results indicate that principals who actively manage social media communications, such as using quick-response features and delivering honest, empathetic messages, successfully build stakeholder trust and control the narrative amid uncertainty. This responsive and collaborative communication model strengthens social relationships and accelerates the adaptation of school community members. These findings align with the theory that effective crisis communication requires a leader's digital competence and interpersonal skills. This research contributes to the development of digital leadership and crisis management theory in education. It provides practical guidance in developing effective communication policies and training for schools in emergencies.